2000
DOI: 10.1046/j.1440-1746.2000.02305.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of Helicobacter pylori infection with atrophic gastritis and intestinal metaplasia

Abstract: These results suggest that atrophic gastritis is not a normal aging process, but instead is likely to be the result of H. pylori infection, while intestinal metaplasia is caused by both the aging process and H. pylori infection. A decreased risk of intestinal metaplasia found in uninfected female subjects may partly explain the lower prevalence of gastric cancer in females than in males.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
3
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 46 publications
3
55
3
1
Order By: Relevance
“…In this study, intestinal metaplasia along with chronic gastritis and H.Pylori positivity was found in two gastric biopsies 3 .…”
Section: Discussionsupporting
confidence: 55%
“…In this study, intestinal metaplasia along with chronic gastritis and H.Pylori positivity was found in two gastric biopsies 3 .…”
Section: Discussionsupporting
confidence: 55%
“…Whereas, atrophic gastritis appeared highly at range of age 41-50 years, intestinal metaplasia at range of age 51-60 years, gastric cancer at range of age 61-70 years, compared to chronic which manifests at early age of 21-40 years. These results are reinforced by the study of Kenji et al [28] which demonstrated the existence of a strong significant positive association between age, H. pylori infection and the risk of gastric atrophy and intestinal metaplasia [28]. Also, Salles et al [29] have revealed that H. pylori infection is a chronic gastric infection increased with age.…”
Section: Discussionmentioning
confidence: 92%
“…They found the rate of atrophic gastritis as 82.9% in the Hp-infected group and as 9.8% in the non-infected group. Similarly, the rates of IM were 43.1% and 6.2% in the infected and non-infected groups, respectively (37,38). Topal et al (39) showed that the greater the intensity of Hp, the greater the degree of chronic gastritis and atrophy; a statistically significant positive correlation was defined between them.…”
Section: Discussionmentioning
confidence: 94%